2022
DOI: 10.1021/jacs.1c11053
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Chemoproteomic Profiling with Data-Independent Acquisition-Based Mass Spectrometry

Abstract: Activity-based protein profiling (ABPP) has emerged as a powerful and versatile tool to enable annotation of protein functions and discovery of targets of bioactive ligands in complex biological systems. It utilizes chemical probes to covalently label functional sites in proteins so that they can be enriched for mass spectrometry (MS)-based quantitative proteomics analysis. However, the semistochastic nature of datadependent acquisition and high cost associated with isotopically encoded quantification reagents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 59 publications
(90 reference statements)
1
72
0
Order By: Relevance
“…We prioritized studies that reported high coverage datasets that measured one or more of the following parameters: (1) total number of cysteines identifiable by the pan-cysteine reactive probes, (2) measurement of cysteine intrinsic reactivity towards iodoacetamide alkyne (IAA, 1) and (3) assaying cysteine ligandability (Figure 1A). We collected a total of nine datasets that fulfilled our criteria (Figure 1B for all datasets used) 2,[4][5][6][7][8][9][10][11] .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We prioritized studies that reported high coverage datasets that measured one or more of the following parameters: (1) total number of cysteines identifiable by the pan-cysteine reactive probes, (2) measurement of cysteine intrinsic reactivity towards iodoacetamide alkyne (IAA, 1) and (3) assaying cysteine ligandability (Figure 1A). We collected a total of nine datasets that fulfilled our criteria (Figure 1B for all datasets used) 2,[4][5][6][7][8][9][10][11] .…”
Section: Resultsmentioning
confidence: 99%
“…With a complete, curated dataset in hand, our next step was to construct the CysDB database and web user interface outlined in Figure 2A. Raw data from prioritized studies 2,[4][5][6][7][8][9][10][11] were pre-processed into a standardized input format for SQL integration (See Table S1 for example data format and required information for future data integration to CysDB). Processed data from these selected sources was ingested and transformed into a database hosted in Google Cloud using MySQL v.8.0.…”
Section: ) Establishing An Sql Database With An Rshiny User Interface...mentioning
confidence: 99%
See 3 more Smart Citations